2010
DOI: 10.1002/chem.201002402
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for the Antiproliferative Activity of Pre‐mRNA Splicing Inhibitor FR901464

Abstract: FR901464 is a natural product isolated from a bacterium source that activates a reporter gene, inhibits pre-mRNA splicing, and shows antitumor activity. We previously reported the development of a more potent analogue, meayamycin, through the total synthesis of FR901464. Herein, we report detailed structure-activity relationships of FR901464 that revealed the significance of the epoxide, carbon atoms in the left tetrahydropyran ring, the Z-geometry of the side chain, the 1,3-diene moiety, the C-4 hydroxy group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 181 publications
(241 reference statements)
6
104
0
3
Order By: Relevance
“…16 Meayamycin B was produced by the Koide group (University of Pittsburgh, USA). 20 ABT-199 and ABT-263 were purchased from Selleckchem (USA). Annexin V-FITC was produced in-house (Southampton CR-UK core protein production facility).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Meayamycin B was produced by the Koide group (University of Pittsburgh, USA). 20 ABT-199 and ABT-263 were purchased from Selleckchem (USA). Annexin V-FITC was produced in-house (Southampton CR-UK core protein production facility).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…16 SSA is a synthetically modified analog of the natural product FR901464, 19 while meayamycin B is prepared by total synthesis. 20 SSA binds to SF3B1 and possibly other members of the splicing factor 3 complex and targets normal splicing in the cell, promoting alternative gene splicing, accumulation of unspliced mRNAs in the nucleus and a decrease in translation. 16 Numerous transcripts have been shown to be down-modulated by SSA-altered splicing in HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…13,22 FR901464 is a potent natural product that inhibits pre-mRNA splicing via SF3b factor binding. 23, 24 We performed human colonyforming unit cell assay using BM mononuclear cells from 4 healthy subjects without and with different concentrations of meayamycin SF3B1 AND MDS 3175 BLOOD, 18 OCTOBER 2012 ⅐ VOLUME 120, NUMBER 16 For personal use only.…”
Section: In Vitro Treatment Of Healthy Bm Cells With Meayamycinmentioning
confidence: 99%
“…5 Second, a non-epoxide analog of meayamycin that still contains the oxygen atom at the C3 position completely lost the activity, with IC 50 values changed from 0.02 nM to >10 000 nM. 11 Although there is no concrete evidence about the influence of the carboxyl moiety at C17 position on the bioactivity of 1, our studies on thailanstatins suggested that this moiety is critical to compound stability under weak alkaline conditions. 7 Collectively, the absence of an epoxide moiety at C3 position and a hydroxyl group at C4 position of 1 most likely contributes to its weak cytotoxicity, which, in turn, supports the importance of those functionalities in FR901464 class of natural or synthetic compounds.…”
mentioning
confidence: 75%
“…It was reported that a loss of C4 hydrogen bond donor decreases the cytotoxicity of meayamycin B (a synthetic FR901464 analog) about fourfold. 11 The importance of the C3 epoxide moiety for bioactivity has been documented in two independent studies. First, substitution of the C3 epoxide moiety in FR901464 by a terminal methylene group decreases the cytotoxicity about fivefold.…”
mentioning
confidence: 99%